Effect of dietary organic selenium on fatty acid composition in nutria (Myocastor coypus Mol.) livers. Issue 2 (18th January 2013) - Głogowski, Robert; Czauderna, Marian; Rozbicka‐Wieczorek, Agnieszka; Krajewska, Katarzyna A.
Abstract Young, female nutrias (n = 13) were fed a diet supplemented with 0.36 mg/kg selenium in selenium‐enriched yeast (SeY; Sel‐Plex; Alltech, Inc., Nicholasville, KY) for 60 days (total Se concentration in the basal diet was ∼0.1 mg/kg). Concentrations of fatty acids (FA) in the liver were compared to those of nutrias on a control diet (n = 11). Animals were sacrificed at 8 months of age and liver samples (approximately 30 g) were collected. The gas‐chromatographic analysis of tissue samples from the experimental group revealed a significant decrease in saturated fatty acids (p<0.001), monounsaturated fatty acid (p = 0.006), and polyunsaturated fatty acid (PUFA) (p = 0.02) compared to controls. The linoleic and linolenic acids, which are precursors of n‐6 and n‐3 PUFA, respectively, were significantly lower (p = 0.01 and p<0.001, respectively) in the supplemented group. The n‐6 to n‐3 PUFA ratio was significantly affected (p = 0.001) by the SeY dietary supplement (13.17 vs. 8.93, respectively).